Economic Value Added and Market Value Added as A Measuring Tool for Financial Performance - Silvia, Rina; Wangka, Novriani (International Journal of Social Science and Business, 2022)
Every company has its own goals to be achieved. However, the main goal of a company is to earn profits and benefit shareholders. This study aims to analyze the financial performance of product distributors PT. Unilever, Tbk North Halmahera Branch, namely PT. Agung Maluku branch of North Halmahera using the Economic value added (EVA) method is an important innovation because in addition to not only formulating modern financial concepts, but the up-to-date implications of this concept have helped managers to better understand financial goals and help achieve these goals by easier access for managers to understand financial aspects that are sometimes complicated to understand for decision making and the Market Value Added (MVA) method helps managers to focus on valuable activities and to evaluate performance based on maximizing company performance evaluation. Observations were made on the product distributor PT. Unilever, Tbk North Halmahera Branch (PT Agung Maluku) during 2018-2019 by observing quarterly financial statements 1,2 and 3. Descriptive statistical analysis was used to find EVA and MVA values. Based on the analysis of financial performance using the EVA and MVA methods of PT. Agung Maluku, it produces a positive value which means the company is able to create added economic value to its investors, even though it is categorized as a company that is just starting out in the North Maluku region.